2000
DOI: 10.2337/diacare.23.9.1348
|View full text |Cite
|
Sign up to set email alerts
|

Insulin is an independent correlate of plasma homocysteine levels in obese children and adolescents.

Abstract: OBJECTIVE -The aim of the study was to investigate whether anthropometric and metabolic risk factors for coronary heart disease (CHD) contribute to the variation in homocysteine levels in obese children and adolescents.RESEARCH DESIGN AND METHODS -A total of 84 children and adolescents were assessed for fasting total homocysteine, methylenetetrahydrofolate reductase polymorphism (C677T mutation), folate and vitamin B 12 status, and anthropometric and metabolic risk factors for CHD.RESULTS -No significant sex d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
2
6

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 16 publications
5
52
2
6
Order By: Relevance
“…At present only two studies have evaluated the effects the of C677T polymorphism of 5,10-methylentetrahydrofolate reductase in subjects with insulin resistance and no significant correlations were found between this polymorphism and homocysteine levels and/or common features of insulin resistance (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…At present only two studies have evaluated the effects the of C677T polymorphism of 5,10-methylentetrahydrofolate reductase in subjects with insulin resistance and no significant correlations were found between this polymorphism and homocysteine levels and/or common features of insulin resistance (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Tungtrongchitr et al (2003), reported that obese Thai subjects have lower serum folate than normal weight subjects. A study of obese adolescents in Austria (Gallistl et al, 2000) reported that serum folate correlated inversely with BMI. However, no significant differences in serum folate in overweight and normal weight Brazilian adolescents (Hirsch et al, 2005), or obese and normal weight adults in Israel (Reitman et al, 2002) were seen.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the MTHFR C677T causing mild HHCY is an important genetic risk factor for CVD (9). However, some studies reported no association between MTHFR genotype and plasma HCY levels (10).…”
Section: Introductionmentioning
confidence: 99%